A Case Study on Wadas Community Social Movement: Community Resistance Movement Against Mining Development - Misran, Misran; Asriadi, Asriadi; Abhipraya, Fairuz Arta; Isolana, Jack B.; Efendi, David; Akbar, Paisal (Humanus, 2023)
This study aims to analyze the social movements of the Wadas community related to mining development in Wadas Village. Data sources were obtained by capturing news related to hashtags and at-signs, which Twitter social media users widely use to support resistance and rejection by Wadas people. This study uses a qualitative research method with a case study approach. Data analysis used the NVivo12 software application to visualize the data in graphs, images, and word frequency. The research findings show that the plan to build the Bener Dam in Purworejo District and Wonosobo Regency has experienced a very significant rejection with the circulation of two social movements on social media, Twitter, in the form of hashtags and at-signs as evidence of resistance to the mining project located in Wadas village. #Wadasmelawan is the most popular hashtag often echoed on Twitter social media with a percentage of 3.38%. The Wadas community social movement subsequently used at-sign @Ganjarpranowo, who is also highlighted in the public sphere and social media, is required to resolve mining conflicts due to permits Location Determination (IPL) for andesite mining from the Governor of Central Java Province. Two Wadas social movements using hashtags and at-signs invite a reasonably high response on Twitter users with as many as 89.34% tweets. This means that the community's resistance to mining in Wadas is very significant in getting support from the public.